Trends in mental health service utilization among LGB+ college students - Bourdon, Jessica L. (J Am Coll Health, 2020)
OBJECTIVES. 1) Compare service utilization among LGB+ and straight-identified students. 2) Assess rates of mental health concerns among LGB+ students only. PARTICIPANTS. Undergraduates (N = 675) reported on their sexual orientation, mental health conditions, and past service providers. METHODS. Logistic regression was used for aim 1 and descriptive statistics for aim 2. RESULTS. LGB+ students were more likely than straight-identified students to seek services for anxiety (odds ratio [OR] = 2.051; p < .01) or depression (OR = 3.058; p < .001) and from a counselor / therapist / psychologist (OR = 2.937; p < .001) or their university’s counseling / health services (OR = 1.933; p < .01). Bisexual students utilized the most services. CONCLUSIONS. Colleges must ensure that programming, outreach, and overall support for the mental health needs of their LGB+ students are being met so that this vulnerable population continues to seek services.